Heat Shock Proteins and Protection Against Ischemic Injury - W. H. Dillmann (Hindawi Limited, 1999)
Heat shock proteins present a complex family of proteins exerting chaperone-like activities that are classified according to their molecular weight. We especially explored protective functions of inducible heat shock protein 70, the mitochondrial heat shock protein 60 and 10, and the small heat shock proteins HSP27 and αB-crystallin against ischemic, reoxygenation-mediated injury using transgenic animals and hearts under in vivo conditions and in isolated cardiac myocyte-derived cells using adenoviral vectors. We noted with great interest that differential protective effects are exerted by specific hsps. For example, alpha-B-crystallin and constitutive hsp70 markedly protect microtubular structure in cardiac myocytes from ischemia-induced injury. Inducible hsp70, hsp60 and hspl0 when coexpressed, and hsp27 and αB-crystallin have an overall protective effect against ischemic injury as determined by the release of enzymes like creatine kinase and LDH. We did not note inflammatory or immune responses elicited by the expression of hsps in transgenic animals and cardiac myocytes. The specific cell types in which hsps are expressed may contribute to the protective effect of hsps versus their inflammatory and immunogenic effects when expressed in other cell types. Infect. Dis. Obstet. Gynecol. 7:55-57, 1999.